Community development methods toward food security the system of rice intensification in Zumalai Subdistrict, Covalima, Timor-Leste - Vicente, Ergilio Ferreira (The Journal of Public Affairs and Development, 2015)
The study was conducted in Zumalai subdistrict, Covalima in Timor-Leste to analyze the contribution of the System of Rice Intensification (SRI) program. The program was implemented through community development methods, namely: community education, community organizing, and community resource management to achieve rice security. Using the Slovin's formula, 24 farmer-groups from Raimea village and 17 from Tashilin village were selected through draw lot sampling. From each farmer-group, five members were randomly chosen to comprise 205 respondents to participate in the household survey. Data were analyzed through descriptive and inferential statistics. The findings revealed that majority of the respondents attended various components of the SRI training. The purposes for joining the SRI group included having access to government facilities and incentives, exchanging experiences, sharing resources and labor among members, and working together. The SRI practices were able to secure communities' environment and maximize the utilization of local resources. The program, which could be sustained with the existing resources in the study sites, could increase rice production. With the increase rice shortage after their involvement in the SRI program. Rice production had been sufficient to feed their families all year round.